Identification of type B-specific and cross-reactive cytotoxic T-lymphocyte responses to Epstein-Barr virus. - Kerr, B M (1996)
Persistent Epstein-Barr virus (EBV) infection is primarily controlled by HLA class I-restricted memory cytotoxic T-cell (CTL) responses which can be reactivated in vitro by stimulation of peripheral blood lymphocytes with autologous lymphoblastoid cell lines. During an investigation of a donor infected by both type A and type B EBV, CTL specific for type B EBV were isolated. The CTL were found to recognize an epitope encoded by the EBNA-6B gene. The minimal epitope sequence was identified as QNGALAINTF, corresponding to residues 213 to 222 in the EBNA-6B protein, and presentation of this epitope was shown to be via HLA B62 (B15). This is the first report of the characterization of an epitope that is EBV type B specific. CTL recognizing sequences common to type A and type B EBV were identified as well. A cross-reactive epitope recognized by these CTL was encoded within the EBNA-6 gene of both type A and type B. This minimal sequence for this epitope was LLDFVRFMGV (residues 284 to 293 in both types), and the epitope was restricted through HLA A*0201. This second epitope sequence overlaps with a published EBV B44-restricted epitope (EENLLDFVRF). The implications of these findings are discussed with respect to the design and efficacy of epitope-based vaccines.